Lateral facies variations in the Triassic Dachstein platform: A challenge for cyclostratigraphy. (29th August 2019) - Samankassou, Elias; Enos, Paul
Abstract: The Triassic Dachstein platform limestone at Steinernes Meer, Salzburg, Austria, includes 611 m of limestone with 222 peritidal cycles overlain by 273 m of subtidal, non‐cyclic and weakly cyclic limestone. Cycle patterns include both shoaling and deepening upward, symmetrical, truncated, and couplets without a depth vector. Beds are laterally discontinuous, and cycle bounding surfaces are laterally variable in the studied strata. Of 558 subtidal and intertidal beds measured, 121 (21.7%) disappear laterally. An additional 73 beds (13.1%) show significant (>10%) lateral variations in thickness. Mean thickness variation is 49%. Both lateral variations and terminations appear to lack a spatial vector. Disappearances toward the inferred platform interior (west) total 10% of the beds. East, toward the platform margin, 11.6% of the beds disappear. Thickness changes occur in 6.5% of beds in each direction. The lack of lateral continuity of beds precludes a simple allocyclic forcing model and is consistent with a non‐eustatic component to stratification. Erosion of intertidal intervals is the process that can be most readily documented. Non‐uniform rates of production, transport and distribution of sediments, superposed on stratigraphic sequences driven by eustasy, probably also contributed to the complex cycle patterns recorded in the Dachstein. Such composites of autocyclic and extrabasinal factors should not be uncritically interpreted as exclusive records of orbital forcing. Lateral discontinuities and thickness variations would also produce inaccuracies in spectral analysis of thickness patterns, typically conducted in search of 'Milankovich frequencies', as well as in construction of Fischer plots to analyse long‐period oscillations in accommodation. Any section subjected to cycle analysis should be examined for lateral changes, to the extent permitted by the exposures, in order to produce the most complete (composite) section possible. Abstract : (A) and (B) Examples of pinchouts and reworking. An intertidal, whitish B horizon, underlying a subtidal, grey C member is well‐developed in (B), but pinches out, by chemical erosion, in (A) (arrow). The breccia to the left in (A) is a soilstone, filling the resulting solution pit, which extends into the underlying subtidal limestone. A shallower solution pit is visible at the right of (B). This CBA‐C succession defines a shallowing‐upward cycle. Steinernes Meer section, 594.6 m. (C) Reddish lens of a palaeosol (A member, arrow) and clast of intertidal B member (whitish) preserved only in karst pockets atop a subtidal member C. (D) Whitish clast of laminated, dolomitic member B reworked into the base of a grey, subtidal C member. Pen in A, B and D is approximately 15 cm long. Scale in C is in centimetres and inches, foreshortened by the angle of view.